Alternative payment models in Dutch hospital care: what works, how, why and under what circumstances? Protocol for a realist evaluation study - Frank Eijkenaar; Celine Maria Rosanne Hendriks; Miel Antonius Petrus Vugts; Jeroen Nathan Struijs; Daniëlle Cattel (BMJ Open)
Introduction The predominant provider payment models in healthcare, particularly fee-for-service, hinder the delivery of high-value care and can encourage healthcare providers to prioritise the volume of care over the value of care. To address these issues, healthcare providers, payers and policymakers are increasingly experimenting with alternative payment models (APMs), such as shared savings (SS) and bundled payment (BP). Despite a growing body of literature on APMs, there is still limited insight into what works in developing and implementing successful APMs, as well as how, why and under what circumstances. This paper presents the protocol for a study that aims to (1) identify these circumstances and reveal the underlying mechanisms through which outcomes are achieved and (2) identify transferrable lessons for successful APMs in practice.Methods and analysis Drawing on realist evaluation principles, this study will employ an iterative three-step approach to elicit a programme theory that describes the relationship between context, mechanisms and outcomes of APMs. The first step involves a literature review to identify the initial programme theory. The second step entails empirical testing of this theory via a multiple case study design including seven SS and BP initiatives in Dutch hospital care. We will use various qualitative and quantitative methods, including interviews with involved stakeholders, document analysis and difference-in-differences analyses. In the final step, these data and the applicable formal theories will be combined to test and refine the (I)PT and address the research objectives.Ethics and dissemination Ethical approval has been granted by the Research Ethics Review Committee of Erasmus School of Health Policy and Management (Project ID ETH2122-0170). Where necessary, informed consent will be obtained from study participants. Among other means, study results will be disseminated through a publicly available manual for stakeholders (eg, healthcare providers and payers), publications in peer-reviewed scientific journals and (inter)national conference presentations.